India & Pakistan : The Cost of Conflict and the Benefits of Peace - Ali Durrani, Mahmud, Maj. Gen. Retd.; Foreword by Bhushan, Bharat (Karachi Oxford University Press, 2001)
This is a concise study of the India-Pakistan problem. It analyzes how the unresolved conflict is eating into the resources of the two countries and impeding their social and economic development. It is intended for students of international relations and strategic studies.
Include Tables, Graphs and Endnotes.
Keywords: Pakistan -- India -- International relations -- Armed Forces--Appropriations and expenditures -- Diplomatic relations -- South Asian cooperation